The role of defects in the photoconversion of 2-propanol on rutile titania: Operando spectroscopy combined with elementary studies - Kräuter, Jessica; Franz, Evanie; Waidhas, Fabian; Brummel, Olaf; Libuda, Jörg; Al-Shamery, Katharina (Journal of Catalysis, 2022)
Previous studies on the reaction chemistry of 2-propanol at rutile powders in liquid phase as well as at TiO2(1 1 0) surfaces under UHV conditions, both with low reduction degree, exhibited that partial photo oxidation is observable in the presence of oxygen, however, with low yields. Here, we show that at highly reduced surfaces a partial photo oxidation of 2-propanol is not only possible in the presence of oxygen but also in coadsorption with water or even without coadsorbates below room temperature. Thermally, only the conversion towards propane and propene was observed at temperatures above 550 K. Liquid Phase experiments further showed that the coadsorbate influences the acetone yield of the partial photo oxidation. While in the presence of oxygen an increasing acetone conversion was observed, the acetone yield is reduced in the presence of water in accordance with the hypothesis of an active site blocking by water.
CRIS-Team Scopus Importer:2022-02-04
Keywords: Acetone; Isopropanol; Liquid Phase; Model Catalysis; PC-IRRAS; Photo Oxidation; Rutile TiO; UHV; UV Irradiation